1992
DOI: 10.1073/pnas.89.3.905
|View full text |Cite
|
Sign up to set email alerts
|

Host-cell-phenotype-dependent control of the BCR2/BWR1 promoter complex regulates the expression of Epstein-Barr virus nuclear antigens 2-6.

Abstract: (7). This is reflected by the decrease or disappearance of BL-associated CD10 and CD77 markers and the appearance of activation markers. EBNAs 2-6 and LMPs 1, 2a, and 2b are upregulated as well. Nasopharyngeal carcinoma (NPC) represents yet a third type of EBV-host cell interaction. EBNA 1 is always expressed but EBNAs 2-6 are not. LMP 1 is detected in some 65% of NPCs (9).We have found (10, 11) that somatic cell hybrids derived from the fusion of EBV-carrying group III BL lines or LCLs with non-B-cell lines d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
43
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 20 publications
6
43
0
Order By: Relevance
“…FpQUK(557) constituted 1-6 % of the Kcontaining transcripts in induced cell lines (Table 2). RT-PCR with primers Q1 and K2 generated an amplification product that hybridized to the U and K probes, reflecting this small proportion of Fp-initiated transcripts spliced to the EBNA1-specific splice acceptor site in BamHI K. Induction of Rael cells with 5-azacytidine is known to up-regulate Cp\Wp-initiated transcription (Altiok et al, 1992 ;Jansson et al, 1992), shown here by the increased amounts of the protected UK(332) and U(172) fragments and the appearance of a specific amplification transcript that is initiated upstream of the BamHI f/K cleavage site, passing through BamHI K directly into the EBNA1-encoding K exon. The K(350-370) fragments represent transcripts that contain the part of BamHI K upstream of the splice acceptor site for BKRF1, most likely corresponding to a lytic BRRF2 transcript.…”
Section: Fp Activity Is Up-regulated Upon Induction Of the Virus Lytimentioning
confidence: 99%
“…FpQUK(557) constituted 1-6 % of the Kcontaining transcripts in induced cell lines (Table 2). RT-PCR with primers Q1 and K2 generated an amplification product that hybridized to the U and K probes, reflecting this small proportion of Fp-initiated transcripts spliced to the EBNA1-specific splice acceptor site in BamHI K. Induction of Rael cells with 5-azacytidine is known to up-regulate Cp\Wp-initiated transcription (Altiok et al, 1992 ;Jansson et al, 1992), shown here by the increased amounts of the protected UK(332) and U(172) fragments and the appearance of a specific amplification transcript that is initiated upstream of the BamHI f/K cleavage site, passing through BamHI K directly into the EBNA1-encoding K exon. The K(350-370) fragments represent transcripts that contain the part of BamHI K upstream of the splice acceptor site for BKRF1, most likely corresponding to a lytic BRRF2 transcript.…”
Section: Fp Activity Is Up-regulated Upon Induction Of the Virus Lytimentioning
confidence: 99%
“…A number of studies have shown that the type III latency EBNA gene promoters, Cp and Wp, are inactivated by CpG methylation during type I latency (2,10,22,44,49,62,69), while Qp is at the center of a hypomethylated island and remains active (73). Although evidence strongly suggests that methylation of Cp and Wp is absolutely required for EBV to stably maintain the type I and II latency programs (73), almost nothing is known about the specific trans-acting factors which regulate transcription from Qp.…”
Section: Epstein-barr Virus (Ebv) Infection In Immunocompetentmentioning
confidence: 99%
“…This discrepancy may be due to the different passage history of the cells used. While Cp activity is regulated by both CpG methylation (Altiok et al, 1992;Minarovits et al, 1994;Robertson et al, 1995;Salamon et al, 2001;Bakos et al, 2007) and histone modifications (this study), Qp is unmethylated independently of its activity (Tao et al, 1998;Salamon et al, 2001). We observed that similar to active Cp, active Q promoters in lymphoid and epithelial cells are also located on an acetylation island enriched in AcH3 and AcH4.…”
mentioning
confidence: 55%
“…Mutu-BL-I-Cl-216 maintains the phenotype of BL biopsy cells and expresses EBNA 1 and the small EBV-encoded RNAs, EBER 1 and 2, but EBNA 2-5 and latent membrane proteins (LMPs) cannot be detected in this clone (type I latency, Cp off, Qp on). In contrast, Mutu-BL-III-Cl-99 has a lymphoblastoid phenotype and expresses all six EBNAs, EBER 1 and 2, and LMP 1 and 2 (type III latency, Cp on, Qp off) (Gregory et al, 1990;Altiok et al, 1992;Bakos et al, 2007). The BL line Rael (latency I) and the lymphoblastoid cell line (LCL) CB-M1-Ral-STO (latency III) also carry the same EBV strain (Ernberg et al, 1989).…”
mentioning
confidence: 99%
See 1 more Smart Citation